INFLUENCE OF CASH AND CURRENCY ROUND DESCRIPTION OF PROFITABILITY IN MANUFACTURING COMPANY LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2012-2016 - Suyatni suyatni (University of Riau Kepulauan, 2022)
The purpose of this study is to determine the effect of the variable (X1) is cash turnover and variable (X2) is the turnover of receivables against (Y) ie profitability (return on asset). Which becomes the object of this study is the company in the LQ 45 index listed on the Stock Exchange Indonesia period 2012- 2016. In this research, sampling technique is done by purposive sampling method which yield 75 data. Data analysis techniques using SPSS (statistical package for the social scince) version 15.0. The result of this research is cash turnover (X1) have significant effect to return on asset at company that exist in Indonesian Stock Exchange with significant value t test less than 0,05 or 0,002 0,05, receivable turn over (X2) have significant effect to return On assets in companies in the Indonesia Stock Exchange, with a significant value of t test less than 0.05 or 0.005 0.05. Together cash turnover (X1) and receivable turnover (X2) have significant effect on profitability (return on asset) with significant valueof F0,000 0,05 test.Keywords: Cash turnover, receivable turnover, profitability.